HERMENEUTIKA AL-QUR’AN Al-SYATIBi : Metode Tafsir Al-Qur’an dengan Maqashid al-Syari’ah - Ahzaniah, Ahzaniah; Nursyamsu, Nursyamsu (Jurnal AlifLam Journal of Islamic Studies and Humanities, 2021)
The Qur'an with the basic assumption as the idea of ​​God that is eternal, universal, and trans-historical, when it has to be communicated to humans who live historically, then the basic content of the Qur'an must of course adapt to the character of the Arabic language and culture that was a historical reality at the time. The research departs from the many developments of methods and approaches that are so diverse in the interpretation of the Qur'an, so that it often causes debate among commentators. This study is basically an attempt to find out how maqa>shid al-Shari>'ah hermeneutics is a method in the interpretation of the Qur'an and how to apply maqa>shid al-Shari>'ah in the interpretation of the Qur'an. . This study aims to answer these two problems. The nature of this research is qualitative and uses the hermeneutical-analytic method, namely by analyzing the data in the hermeneutic circle and then drawing various conclusions. The data obtained will be analyzed in accordance with scientific theories with the provisions in the analysis guidelines and in accordance with the rules of writing scientific papers. The results show that the maqa>shid al-Shari>'ah hermeneutic method in interpretation cannot ignore three important horizons in hermeneutics, namely text, author, and reader. So the resulting form of interpretation will not only reveal the meaning of the text but will emphasize maqa>shid. While in the application, namely with ta'li>li and istisla>hi patterns. The pattern is considered by the qiya>s and maslaha>h mursala>h methods in ushu>l fiqh.